2020
DOI: 10.1016/j.eclinm.2020.100429
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intensive speech treatment on intelligibility in Parkinson's disease: A randomised controlled trial

Abstract: Background: More than 6,000,000 individuals worldwide are diagnosed with Parkinson's disease (PD). Nearly 90% develop speech signs that may substantially impair their speech intelligibility, resulting in losses in their communication and quality of life. Benefits of intensive speech treatment have been documented for a range of speech signs. However, the critical question of whether speech is more intelligible after treatment has not been investigated in a randomised controlled trial (RCT). We hypothesised tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 67 publications
6
62
0
3
Order By: Relevance
“…Transcription accuracy, considered an objective measure of intelligibility (Hustad, 2006), was calculated as percentage of words correctly transcribed. Orthographic transcriptions were considered correct if words matched the target exactly or if differences were due to homonyms or obvious misspellings (Cannito et al, 2012;Hustad, 2007;Levy, Moya-Galé, Chang, Freeman, et al, 2020). Mean naturalness ratings were calculated from the VAS responses.…”
Section: Perceptual and Acoustic Analysismentioning
confidence: 99%
“…Transcription accuracy, considered an objective measure of intelligibility (Hustad, 2006), was calculated as percentage of words correctly transcribed. Orthographic transcriptions were considered correct if words matched the target exactly or if differences were due to homonyms or obvious misspellings (Cannito et al, 2012;Hustad, 2007;Levy, Moya-Galé, Chang, Freeman, et al, 2020). Mean naturalness ratings were calculated from the VAS responses.…”
Section: Perceptual and Acoustic Analysismentioning
confidence: 99%
“…Only one RCT is available on the rehabilitation effect specifically for early PD patients. Levy and colleagues ( 18 ) found that only the high-intensity voice treatment, Lee Silverman Voice Treatment (LSVT) LOUD®, resulted in significant improvements in intelligibility for patients with mean H&Y 2.1. This was compared to patients receiving a high-intensity articulation treatment or no treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The quality assessment using the Downs and Black scale shows high quality for 7 22,27,2933 of the included studies and fair for 8 21,2429,34,35 of the studies. However, when Cochrane Risk of bias Assessment was applied, the risk of bias shown is generally low.…”
Section: Resultsmentioning
confidence: 98%
“…Among the included studies, five studies 23,24,28,33,34 compared speech and language therapy to no treatment; and five studies 21,2527,31 compared speech and language therapy to control treatment (Respiratory effort treatment). Additionally, four studies 29,30,32,35 included three groups, (Two different groups of speech and language therapies and a non-treatment group).…”
Section: Resultsmentioning
confidence: 99%